2019
DOI: 10.1002/14651858.cd005027.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for morphea

Abstract: Trusted evidence. Informed decisions. Better health. Cochrane Database of Systematic Reviews Analysis 10.1. Comparison 10 Polymerized collagen intralesional injection (0.2 to 1.0 mL / 1.66 to 8.3 mg weekly) × Methylprednisolone subcutaneous injection (maximum dose of 20 mg or 5.0 mL monthly) plus placebo intralesional injection, Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 56 publications
(12 reference statements)
0
34
0
22
Order By: Relevance
“…Some therapeutic regimens used in morphea with variable efficacy include systemic steroids, methotrexate, phototherapy, mycophenolate mofetil, hydroxychloroquine, cyclosporine, and abatacept; however, the most effective treatment, especially in more severe types of the disease, is the combination of methotrexate and pulsed corticosteroids (5,6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Some therapeutic regimens used in morphea with variable efficacy include systemic steroids, methotrexate, phototherapy, mycophenolate mofetil, hydroxychloroquine, cyclosporine, and abatacept; however, the most effective treatment, especially in more severe types of the disease, is the combination of methotrexate and pulsed corticosteroids (5,6,11).…”
Section: Introductionmentioning
confidence: 99%
“…52 A systematic review of 62 pediatric and adult with active morphea showed that MD-UVA1 (50 J/cm 2 ), low dose-UVA1 (LD-UVA1) (20 J/cm 2 ), and NB-UVB five times a week for eight weeks has the same effectiveness. 53 Case reports of three patients with localized scleroderma who received UVA1 with a total dose of 540-1800 J/cm 2 showed improvement of collagen fibers texture with reducing of their size. 54 The Single Hub and Access Point for Pediatric Rheumatology in Europe (SHARE) recommends MD-UVA1 in children with localized scleroderma due to its effectiveness in improving tenderness and reducing skin thickness.…”
Section: Scleroderma (Loe Ii)mentioning
confidence: 97%
“…Some environmental factors like silica or organic solvents may play an important role. It may be also triggered by viral or bacterial (Borelia burgdorferi) infections [14].Genetic factors have been also implicated [1]. Some forms of morphea are activated by trauma or associated with an autoimmune process.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%